2002
DOI: 10.1007/s00276-002-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

The anatomical relationship of the aortic bifurcation to the lumbar vertebrae: a MRI study

Abstract: The objective of this study was to determine the level of the aortic bifurcation in relation to the lumbar spine by MRI and the effect of lumbosacral anomalies on the aortic bifurcation. A prospective study of 441 patients was performed. Sagittal MR images of the entire spine were obtained along with the standard protocol for imaging of the lumbar spine. The vertebrae were counted caudally from C2 instead of cranially from the presumed L5 vertebra. The aortic bifurcation in relation to the lumbar vertebrae was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…It was also reported by other studies (4, 6, 22) and they suggested that if these structures were located outside of the frequent sites, the presence of LSTV should be suspected. However, when using the lumbar MRI alone, we defined vertebral levels incorrectly in 14.1% of the patients.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It was also reported by other studies (4, 6, 22) and they suggested that if these structures were located outside of the frequent sites, the presence of LSTV should be suspected. However, when using the lumbar MRI alone, we defined vertebral levels incorrectly in 14.1% of the patients.…”
Section: Discussionsupporting
confidence: 55%
“…In MRI studies by Lee et al (6) and Chithriki et al (22), AB was found at L4 body in 83% and 67% of the cases, respectively. Another study by Lee et al (4) revealed that in the normal group, the AB was most prevalent between the upper half of L4 body and L4-5 disc in 94.8% of the cases.…”
Section: Discussionmentioning
confidence: 86%
“…Anatomical landmarks such as the aortic bifurcation, the transitional points of the abdominal aorta to the bilateral common iliac arteries, the cross point of the right ureter and the pelvic brim, and the cross point of the sigmoid mesentery and the pelvic brim were selected for morphometric analysis. The aortic bifurcation and the right ureter were easily identifiable by inspection or palpation under the retroperitoneum even during surgery and have been used successfully as anatomical landmarks in previous radiologic [5,16] and dissection studies [18,21]. The root of the sigmoid mesentery was selected because the left ureter was covered by the root of the sigmoid mesentery [6].…”
Section: Discussionmentioning
confidence: 99%
“…They found that BAA was at the upper half of the L4 vertebral body in 45% of patients, at the lower half of L4 in 38% of patients, at the L3–L4 intervertebral disk space in 10% of patients, at the L4–L5 intervertebral disk space of the level in 4% of patients, and at the lower half of L3 in 2% of patients. Chithriki et al [ 2 ] assessed the level of BAA in relation to the lumbar spine using MRI. They noted that BAA was found at the L4 vertebral body in 67% of patients, at the L3/L4 vertebral bodies in 13% of patients, and at the L3 vertebral body in 9% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular variations of the bifurcation of the abdominal aorta (BAA) are rare, and they are usually discovered incidentally by manifestations of chronic lower limb ischemia. The most common site of BAA was at the L4 vertebra (67–83%) [ 1 , 2 ]. The BAA can be at an elevated level of the L3 vertebral body in rare cases [ 1 3 ].…”
Section: Introductionmentioning
confidence: 99%